The importance of breastfeeding on the development of the mother-child relationship from an emotional point of view - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Neagu, Verginia Roxana (Technium Social Sciences Journal, 2021)
Breastfeeding is known to have positive effects on the health and nutrition of infants and has been associated with increased subsequent cognitive ability and educational achievement. It is also believed to encourage the development of a "bond" between mother and child in early childhood. The benefits of breastfeeding on mothers and children are well known, with growing evidence that prolonged breastfeeding brings health and financial benefits. Despite the evidence that there are considerable benefits of breastfeeding, there are still gaps in understanding why many women have difficulty initiating and maintaining breastfeeding. Unfortunately, our country is at the end of the European ranking. Practically, in the vast majority of maternity hospitals, women do not receive the necessary help to start breastfeeding and are even discouraged by the medical staff, who in most cases are guided by outdated and erroneous information. Moreover, mothers need encouragement and emotional support from the medical staff and the family, being in a sensitive period, with major physical and mental changes. Thus, the present study was designed to explore the potential relationships between breastfeeding and the development of the mother-child emotional dyad. In the first chapter we presented the importance of breastfeeding, the risks of not breastfeeding and the development of emotions in the first year of life. I also went through the stages of developing the mother-child relationship and described the child's temperament. In the second chapter we gave the definition of the term attachment and we identified the main types of attachment after J.Bowlby. Next we defined the parental styles and we identified their main types. We also defined emotional stability and postpartum depression. In chapter 3 we presented the research objectives and the 5 formulated hypotheses. Later I described the 4 chosen working tools, among which my own tool. At the end of this chapter I described the group of participants. In the fourth chapter we introduced the statistical processing of data and their interpretation. The last chapter contains the conclusions of the study.